MENINGKATKAN HASIL BLAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Pertiwi, Putri Indah; Sari, Imelda; Maharani, Siti Dewi (Universitas Negeri Medan, 2023)
This classroom action research aims to describe the use of the Problem Based Learning learning model in an effort to improve student learning outcomes which was carried out in class IV of SD Negeri 238 Palembang on the content of the Indonesian language subject, material on transitive sentences and class IV intrasynthetic sentences. This type of research uses classroom action research (PTK) with data collection techniques consisting of interviews, tests and observations. Data collection procedures are carried out through tests at the end of each cycle and observations during learning. The average learning outcomes of students in cycle I, cycle II, cycle III have increased. In cycle I the average student score was 67.16 with learning completeness 63%. In cycle II the average student score was 76.04 with learning completeness 77%. And in cycle III the average student score was 80.03 with learning completeness of 87%. The results of this research show that the application of the Problem Based Learning learning model can improve learning outcomes in Indonesian Language Subjects.